Deus, mente e mundo: sobre os conceitos de complicatio, imago e explicatio a partir do diálogo "De mente" de Nicolau de Cusa - Andrade Filho, Osvaldo Ferreira de (2013)
This work deals with the way how the three themes of traditional metaphysics, namely, God, man, and the world, are rethought through the philosophical speculation of German cardinal Nicholas of Cusa (1401-1464). Due to the comprehensiveness of this subject, our dissertation had as a starting point and constant reference the book that the philosopher wrote in 1450, Idiota. De mente, the second written work that makes up the series of the Idiota (Idiotae libri), whose discussion is developed around the theme of the human mind. From the dialogue of the mind we have built our reflection on some issues and theoretical foundations presented in Idiota. De sapientia and De docta ignorantia, extending it to little more than that. According to Nicholas of Cusa, the human mind, in its creative character in the image of the divine mind, transcends the purely functional considerations commonly assigned to it, that is, those that regard its cognitive nature and epistemological role. In addition to these aspects, Cusanus understands the humana mens as a point of articulation of two other main themes of his metaphysics: God and the world. In this context, through the concepts of complicatioexplicatio and imago, as well as with the intercession between the themes of man as imago Dei and the reason of the microcosm, we present here an introduction to Cusan metaphysics